A Christian college in a food truck? Christian study centers and moral formation. (March 2021) - Hansen, Andrew
The task of moral formation has long been an important purpose of higher education in the United States. However, pluralism and lack of moral consensus within secular universities present significant challenges to accomplishing this task. One possible solution is Christian study centers, which offer thick moral cultures that can form students at secular universities within the Christian tradition. Anselm House's Fellows Program at the University of Minnesota illustrates such a context and suggests avenues for future research.